Global hotspots of conversion risk from multiple crop expansion. (February 2021) - Zhang, Y.; Pang, M.; Dickens, B.L.; Edwards, D.P.; Carrasco, L.R.
Abstract: Habitat loss caused by agricultural expansion is a major threat to global biodiversity. A key question is which specific crops will lead to future hotspots of crop conversion. We develop a spatially explicit land-rent contagion model of agricultural conversion for the top crops in terms of global area and value of production, and evaluate crop-specific threats under scenarios of current yields and closed yield gaps. We show that the ecoregions of the Western Congolian swamp forests (coconut), Northwestern Congolian lowland forests (oil palm, maize, rice), and Southern American Pacific mangroves (oil palm) present the highest extinction potential for birds and mammals. Closing yield gaps is able to reduce bird and mammal extinctions by 20% and 6%, respectively, and is most effective for rice, soybean and wheat. This provides direction of which crops to be targeted by future intensification policies. Corruption and one-party states appear to protect many of the remaining tropical natural habitats from crop expansion. Once corruption is improved, protected area network planning prior to conversion threats is crucial to preserve global biodiversity. Highlights: A spatially explicit land-rent contagion model projects crop conversion potential. Crop expansion threatens remaining tropical natural habitats with high biodiversity. Closing yield gaps is able to reduce carbon emissions and bird and mammal extinctions. Yield gap closure of rice, soybean, and wheat prevents most crop expansion projected.